2013
DOI: 10.1371/journal.pone.0062668
|View full text |Cite
|
Sign up to set email alerts
|

The Chromatin Remodeling Factor CSB Recruits Histone Acetyltransferase PCAF to rRNA Gene Promoters in Active State for Transcription Initiation

Abstract: The promoters of poised rRNA genes (rDNA) are marked by both euchromatic and heterochromatic histone modifications and are associated with two transcription factors, UBF and SL1 that nucleate transcription complex formation. Active rRNA genes contain only euchromatic histone modifications and are loaded with all components of transcriptional initiation complex including RNA polymerase I. Coupled with histone acetylation and RNA polymerase I targeting, poised promoters can be converted to active ones by ATP-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Accordingly, it has been shown that UV-and hypoxiamediated acetylation of histone H4 at the promoters of certain responsive genes is impaired in CSB-HF, and that this is due to defective recruitment of the HAT p300 to the acetylation site (19,20). A similar function of CSB has also been demonstrated for another HAT, p300/CBP-associated factor (PCAF), because it is recruited to rRNA promoters in a CSB-dependent manner to enable transcription initiation (50). We believe that the impact of CSB on acetylation of nuclear targets might be relevant for its role in regulating chromatin remodeling (51,52).…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, it has been shown that UV-and hypoxiamediated acetylation of histone H4 at the promoters of certain responsive genes is impaired in CSB-HF, and that this is due to defective recruitment of the HAT p300 to the acetylation site (19,20). A similar function of CSB has also been demonstrated for another HAT, p300/CBP-associated factor (PCAF), because it is recruited to rRNA promoters in a CSB-dependent manner to enable transcription initiation (50). We believe that the impact of CSB on acetylation of nuclear targets might be relevant for its role in regulating chromatin remodeling (51,52).…”
Section: Discussionmentioning
confidence: 87%
“…For example, in human cells, trimethylation of H3K36 has been suggested to promote DNA end resection and repair of DSBs via HR (Aymard et al , ; Pfister et al , ) and modification of H3K9 has been implicated in the DSB response in heterochromatin that is preferentially repaired by HR (Chiolo et al , ). CSB has been found, in different contexts, to associate with numerous chromatin modifying and remodeling factors such as NuRD (Xie et al , ), SMARCA5 (Aydin et al , ) as well as histone methyltransferase G9A (Yuan et al , ) and acetyltransferase PCAF (Shen et al , ), while the yeast homolog of CSB, Rad26, has been reported to genetically interact with the H3K36 methyltransferase SET2 (Jha & Strahl, ).…”
Section: Discussionmentioning
confidence: 99%
“…The EMBO Journal Role of CSB in DNA double-strand break repair Nicole L Batenburg et al HR (Chiolo et al, 2011). CSB has been found, in different contexts, to associate with numerous chromatin modifying and remodeling factors such as NuRD (Xie et al, 2012), SMARCA5 (Aydin et al, 2014) as well as histone methyltransferase G9A (Yuan et al, 2007) and acetyltransferase PCAF (Shen et al, 2013), while the yeast homolog of CSB, Rad26, has been reported to genetically interact with the H3K36 methyltransferase SET2 (Jha & Strahl, 2014). Although transcription inhibition did not abolish the impairment of CSB-KO cells in IR-induced Rad51 foci formation and ATM activation, it abrogated the accumulation of CSB at sites of DNA DSBs.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin assembly and remodeling are believed to be epigenetic switches responsible for the on/off state of rRNA genes34353637. In interphase nuclei, most of 45 S rRNA genes are compacted into heterochromatic chromocenters and the florescent in situ hybridization (FISH) signals manifest as compacted spots in WT maize (Fig.…”
Section: Resultsmentioning
confidence: 99%